The ethical and political role of education in overcoming the enviromental crisis: an analysis gramscian - Luciane Albernaz de Araujo Freitas; André Luis Castro de Freitas (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
The social environmental crisis reach hazard proportions and it should be thought beyond the physical and biological environment. This is set like a problem that includes the economic, social and politic dimensions in their interrelations, being conditioned to the current civilizing pattern: the capitalism. As theoretical basis, the Marxian thinking and the Transformative Environmental Education assumptions, this article aims to problem the role of the Education to overcome the social environmental crisis to build the Education and especially of a pedagogical practice that is in harmony with the thinking for contributing with the counter-hegemonic process. On this perspective, is problem the Gramscian thinking, specially the politic-ethical role of Education to overcome the social environmental crisis.